Encephalitis of unknown etiology and human rabies in the United States, 1999-2008 - Vora, N. M.; Blanton, J. D.; Holman, R.; Mehal, J.; Petersen, B. W.; Recuenco, S.; Track, D.; Rupprecht, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Encephalitis is a severe neurologic syndrome caused by a variety of infectious and noninfectious pathologies. In many instances a definitive etiology of encephalitis is not identified, but a study of encephalitis in California found that 0.3% of cases referred for further evaluation to a specialized diagnostic facility (Glaser, Gilliam et al. 2003) was due to rabies. Under recognition of human rabies in the United States by healthcare providers may account for missed diagnoses of rabies. The purpose of this investigation was to estimate the number of encephalitis-related deaths in the United States and the proportion due to rabies specifically. We reviewed human mortality data in the United States between 1999-2008 and identified encephalitis-associated deaths using ICD-10 codes. Codes were categorized based on if an etiology of encephalitis was listed or not. We also reviewed all laboratory-confirmed human rabies cases within the United States and its territories that were reported to the Centers for Disease Control and Prevention (CDC) during this same time period. A total of 12,457 cases of encephalitis-associated deaths were identified, of which 8726 (70%) were of unknown etiology. Twenty (0.2%) cases were coded as rabies. During this same time period, 27 confirmed cases of rabies were reported to CDC. Of these 27 cases, 6 of the exposures occurred in countries other than the USA. Dogs were the most commonly reported exposure among imported cases. Of the 21 indigenous cases, 14 were attributable to bats, 4 to tissue/organ transplantation, 1 to a dog exposure in Puerto Rico and 2 from unknown sources. Our findings suggest that the majority of encephalitisassociated deaths in the United States were of unknown etiology. Among the confirmed cases of rabies, the majority who acquired rabies within the United States acquired the infection from wildlife. Nearly 10% of the indigenous cases occurred through an unknown exposure. Healthcare providers should consider evaluating for rabies when a patient develops acute progressive encephalitis of unknown etiology despite routine evaluation or if clinical history is suggestive.